Fast and sensitive HPLC method for the determination of neopterin, kynurenine and tryptophan in amniotic fluid, malignant effusions and wound exudates. (November 2015) - Krcmova, Lenka Kujovska; Cervinkova, Barbora; Solichova, Dagmar; Sobotka, Lubos; Hansmanova, Lenka; Melichar, Bohuslav; Solich, Petr
Abstract: Aim: A new HPLC method for the determination of neopterin, kynurenine and tryptophan using a second-generation monolith stationary phase and high-throughput sample preparation procedure based on microplates was developed and fully validated. Materials & methods: As the stationary phase a monolithic C18 Chromolith high-resolution column with dimensions of 4.6 × 100 mm connected to a monolithic 4.6 × 10-mm security guard was used. Separation was achieved using 15 mM phosphate buffer (KH2 PO4 +K2 HPO4 ·3H2 O at pH 3) and acetonitrile in gradient mode. Results: Target analytes were determined in 5.5 minutes in amniotic fluid, effusions and wound exudates with a limit of quantification (LOQ) of 1.25 nM for neopterin, 2.5 µM for tryptophan and 0.25 µM for kynurenine. Discussion: The method was applied to real clinical sample measurements, and it will be used to monitor neopterin, kynurenine and tryptophan levels in biological fluids to assess the patient response to therapy and clinical status.